Utilisation of Medicinal Plants and Its Implications for Conservation in Omo Biosphere Reserve, Nigeria - Obioh, Gloria I. B. (nee G. U. Ahuama); Illoh, Herbert C.; Isichei, Augustine O. (2014)
Biosphere Reserves are in situ conservation areas created to demonstrate the potential for conservation of biodiversity despite the growing human activities to support development. Currently, local options for forest management and for choice of conservable species have not been fully integrated into the management of biosphere reserves. Our paper aims at identifying the role indigenous knowledge could play in the sustainable management and conservation of biosphere reserves, using Omo Biosphere Reserve, Nigeria as a case study. We thus carried out ethnobotanical studies in the reserve following standard methods. We evaluated the local importance of eight medicinal plants and documented how they are used in the reserve. The species studied were Carpolobin lutea, Dioscorcophyllum cumminsii, Irvingin gabonensis, Myrinnthus arboreus, Sphenocentrum jollyanum, Spondias mombin, Tetrapleura tetraptera and Xylopia aethiopica. Our results show that rather than exotics, there are successful indigenous medicinal species in the biosphere reserve including Irvingia gabonensis, Sterculia rhinopetala and Tetrapleura tetraptera that could be used to support ongoing conservation programmes. These have high potential for maintaining the cultural and ecological resilience of degraded sites in the reserve. We recommend that the integration of local knowledge and practices into national and regional conservation programmes are critical in achieving the purpose for which biosphere reserves were established.